Green Synthesis Of Silver Nanoparticles Of Leaf Extract Of Senduduk Bulu (Clidemia Hirta (L) D.Don) And Exploration Of The Antibacterial Activity - Arvian, Dias Wahyu; Rahmawati, Ismi; Ikasari, Endang Diyah (LPPM Akafarma Sunan Giri Ponorogo, 2025)
Senduduk bulu wild plant contains secondary metabolite compounds which used natural reducing agent on synthesis of silver nanoparticles (AgNPs). This research determine the optimum extract concentration and temperature in the process synthesis of silver nanoparticle, characteristics of silver nanoparticles and antibacterial activity of silver nanoparticles against S.aureus and E.coli. Synthesis of silver nanoparticles senduduk bulu leaf using variations extract concentration and temperature variations. The characteristics of silver nanoparticles senduduk bulu leaf were carried out using a UV-Vis Spectrophotometry, Particle Size Analyzer (PSA) and Scanning Electron Microscopy – Energy Dispersive X-Ray Spectroscopy (SEM-EDS). Antibacterial activity testing used the disc diffusion method. The results of research showed the silver nanoparticles of senduduk bulu leaf were successfully synthesized under optimal conditions an extract concentration of 1% and temperature of 60ºC indicated the colloid color changing to brown and maximum wavelength value of 413 nm with absorbance value of 2.9987. The size of colloidal AgNPs of senduduk bulu leaf was 59.2 ± 1.03 nm; zeta potential value -39.3±0.509 mV. The morphology of the AgNPs of senduduk bulu non uniform shape, the crystal size distribution is 50 – 230 nm with an average of 136 nm. The chemical composition of AgNPs crystals shows that silver (Ag) dominates with a weight concentration of 37.688% and atomic concentration of 7.605% at the peak of the 3 KeV spectrum. Feathered AgNPs had antibacterial activity against S.aureus of 14.1 ± 0.3 mm and E. coli of 13.5 ± 0.2 mm. Keywords: Green Synthesis, Silver Nanoparticle, Senduduk Bulu Leaf, Staphylococcus aureus and Escherichia coli.